A medium frequency transformer design for spot welding machine using sizing equation and finite element analysis - Arslan, Serdal (Array, 2020)
In this study, a medium frequency power transformer has been designed analytically and its sizes have been obtained. The transformer’s analyses were made numerically by 2D AnsysMaxwell Solver software package. The Solver has also helped to study suitable transformer core and winding samples. Unlike medium frequency transformer, which is generally driven by unipolar PWM method, the designed transformer is driven by bipolar PWM method in the study. The core losses were obtained for different core materials (Trafoperm N3 and Amorfous 2605SA1) by AnsysMaxwell numerical and analytical calculations. The calculated losses for no-load working conditions were compared with each other. The designed transformer has been analyzed for its noload and loaded working conditions magnetically. Finally, the radial and axial forces created in the windings have also been examined for loaded working condition.